Application of Supply Chain Management to Improve Economic Potential of Dairy Enterprises - M. Tsemba, Natalia (ExcelingTech, 2020)
The main objective of this research is to propose the effectiveness of dairy supply chain management in economy and to illustrate the current practices of diary supply chain in Russia. A modern analysis of the effective economic development of dairy complexes should also include the economic potential assessment. Currently, there are no unified methodological approaches to the potential evaluation, adapted to the operation specifics of the enterprises, as well as facilities under consideration. When they evaluate the economic potential of a dairy complex, it is necessary to take into account economic and environmental relationships, as these factors affect its sustainable supply chain development. As the evaluation criteria of the enterprise economic potential that form a dairy complex, we need the indicators that will contribute to the development of integration between enterprises supply chains that form a complex.